Uzbek and English Philosophy and Phraseology About Happiness as a Value - Nafisa Farkhadovna Kasimova; Masuma Umarovna Sharipova (Genius Journals, 2022)
The presented article analyses the philosophical and cultural features of phraseological units reflecting the concept of happiness of non-related languages. The main focus has been done on the similarity and identity of ideas about happiness reinforced in phraseological units of the English and Uzbek languages based on dictionaries.
Keywords: Phraseology; Value; Philosophical; Concept Of Happiness